Religious Conversion and the Cessation of Megalithic Practice in the Kelabit Highlands of Sarawak - Nicholas, Gani (UNIMAS Publisher, 2021)
This paper explores the role of religious conversion in the cessation of megalith building among the Kelabit people of the Kelabit Highlands in Sarawak, Malaysian Borneo. The religious conversion and the cessation of megalith building that followed are contextualised within the wider changes that impacted the local or native communities in the interior of Sarawak during the colonial period (1946-1963). More specifically, this article considers the impacts of Christianity on the Kelabit society, and demonstrates the incompatibility of the rituals of megalith or monument building with the ‘newly’ adopted Christian religion, which ultimately contributed to the abandonment of practice. This article contributes not only a better understanding of the cessation of the megalithic practice in the Kelabit Highlands, but also provides a portrayal of a local culture undergoing change during the colonial period of Sarawak.